Stigma Sosial Terhadap Stunting: Tantangan dalam Pencegahan dan Penanganannya di Desa Santur - Sitti Hasbiah; Ilma Wulansari Hasdiansa (Solusi Bersama : Jurnal Pengabdian dan Kesejahteraan Masyarakat, 2025)
Stunting is one of the nutritional problems that still occurs in Indonesia. Stunting treatment does not only refer to medical and nutritional aspects, but is also influenced by social and cultural factors, including the social stigma inherent in families with stunted children. This study aims to examine the forms of social stigma against stunting and its impact on prevention and handling efforts in Santur Village. A descriptive qualitative approach was used in this study with an in-depth interview method with parents, posyandu cadres, local health workers, and village officials. The results of the study show that stigma in the form of negative labeling and feelings of shame often hinder parents from accessing health services and being open to information related to child nutrition. This information shows the importance of a community-based approach that not only focuses on the medical aspect, but also targets changes in people's social views on stunting. By overcoming social stigma, it is hoped that efforts to prevent and handle stunting can run more effectively and comprehensively.